Analisis Butir Soal IPS Kelas V Sekolah Dasar Menggunakan Software ITEMAN - Fitri Alfarisa; Ima Ni'mah Chudari; Firman Robiansyah (Universitas Pendidikan Indonesia Kampus Serang, 2019)
The assessment process did not end by only making questions. They will arrive at the analysis of the questions quality. Item analysis is performed to determine the quality of the questions items arranged. Good quality items will greatly affect the results of the assessment and properly capturing the results of learning. The purpose of this study is to analyze the Social Sciences question items for fifth grade of elementary school using the classic ITEMAN focusing on the characteristics of the level of difficulty, the discrimation power, and the functioning of distractor of items. This research is a descriptive study with quantitative research. Subjects were 370 elementary school students in Serang City. The instrument analuzed was made in the form of 20 items of multiple choices with four answer option. The instrument was validated by the content expert and estimated the reliability by using the KR-20 method by reliability index of 0.75 obtained. The data analysis technique used ITEMAN software to see the characteristics of items that contain the level of difficulty, discrimination power and disctractor’ function. The results showed that 80% of the difficulty level were in the medium category, 90% of the dircrimination power items were in the good category, and 90% of the distractors had well-fuctioned. This result indicated that the question created by teacher for fifth grade of elementary school in Serang City concluded as good category.